1992
DOI: 10.1109/83.199923
|View full text |Cite
|
Sign up to set email alerts
|

Vector quantization for entropy coding of image subbands

Abstract: Vector quantization for entropy coding of image subbands is investigated. Rate distortion curves are computed with mean square error as a distortion criterion. The authors show that full-search entropy-constrained vector quantization of image subbands results in the best performance, but is computationally expensive. Lattice quantizers yield a coding efficiency almost indistinguishable from optimum full-search entropy-constrained vector quantization. Orthogonal lattice quantizers were found to perform almost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Senoo and Girod examined the optimal allocation of bits among the various subhands [8], and their method is employed in the current work. They showed that the minimum overall distortion for a given total rate is achieved when the individual distortion rate curves D,(R,) are of equal slope, that is…”
Section: Bit Allocationmentioning
confidence: 99%
“…Senoo and Girod examined the optimal allocation of bits among the various subhands [8], and their method is employed in the current work. They showed that the minimum overall distortion for a given total rate is achieved when the individual distortion rate curves D,(R,) are of equal slope, that is…”
Section: Bit Allocationmentioning
confidence: 99%
“…Several advantages can be taken from these facts to efficiently design bit allocation and quantization strategies for the different subbands (Senoo and Girod, 1992;Jourdan and Alcaim, 1996). For object-based DWT coding, the number of significant edges is much lower than for regular images, since only one object is being coded (there are no contour edges).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above methods, variable bit rate coding techniques have been used to take advantage of the burstiness of video sources and statistical multiplexing capability of asynchronous transfer mode (ATM) networks [11], [29], [37]. Other researchers have looked into the use of subband coding [10], [18], [25], [30] and wavelets for image compression [2], [3], [8], [40].…”
Section: Introductionmentioning
confidence: 99%